Effects of green coffee supplementation on paraoxonase-1 activity and malondialdehyde levels in Iranian women with polycystic ovary syndrome: a randomized clinical trial - Azam Ildarabadi; Marzieh Vahid-Dastjerdi; Mina Ghorbanpour; Ahmad Mousavi; Mehrnoush Meshkani; Mirsaeed Yekaninejad; Ahmad Saedisomeolia (Osong Public Health and Research Perspectives)
Objectives Polycystic ovary syndrome (PCOS) is a common, heterogeneous clinical syndrome affecting women. Investigating oxidative stress in women is crucial, as it is linked to insulin resistance and endothelial dysfunction. Chlorogenic acid, a bioactive component found in green coffee, has numerous documented health benefits. This study aimed to assess the beneficial effects of green coffee consumption on paraoxonase-1 (PON-1) activity and malondialdehyde (MDA) levels in women with PCOS. Methods This study was a double-blind randomized clinical trial that included 44 patients with PCOS. Participants were randomly assigned to either the intervention or control group. For 6 weeks, the intervention group (n=22) received 400 mg of green coffee supplements, while the control group (n=22) received 400 mg of a starch-based placebo. Anthropometric indices, dietary assessments, and physical activity levels were evaluated before and after the 6-week intervention period. Additionally, blood samples were collected for laboratory analysis. Results Supplementation with green coffee increased PON-1 levels by 3.5 units, a significant finding (p=0.038). Additionally, the intake of green coffee supplements significantly reduced blood cholesterol levels by 18.8 units (p=0.013) and triglyceride levels by 6.1 units (p=0.053). However, no significant differences were observed in the levels of MDA, high-density lipoprotein, low-density lipoprotein, fasting blood sugar, insulin, or homeostatic model assessment of insulin resistance as a result of the intervention. Conclusion Supplementation with green coffee alters PON-1 activity and cholesterol levels in women with PCOS. However, it has no significant impact on MDA levels or glycemic status.